Independent Learning Curriculum for Vocational Students’ Motivation and Interest in Learning English Language - Octaviani, Saly Kurnia; Sari, Arum (Journal of English Language and Education, 2023)
This study aims to analyze the implementation of independent learning curriculum for increasing students’ motivation and interest in learning English language at SMK Analis Kesehatan Nasional, Surakarta. The respondents of this study were 25 eleventh grade students of vocationalsenior high school. This research method in this study applied qualitative research with case study. Techniques of data collection in this study were observation, interview, and closed-ended questionnaires. The results of this study showed that the implementation of independent learning curriculum positively influenced students’ motivation and interest in learning English language. From the results of questionnaire, 90% of students had high motivation in learning English language, 95% students had high curiosity in English language, 90% of students had high interest in learning English language independently, 85% of students preferred fun English language learning method, and 90% of students also had high target to English language learning achievement.